2022
DOI: 10.3390/cancers14235727
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastasis of Breast Cancer: Molecular Mechanisms and Therapeutic Strategies

Abstract: Bone metastasis is a common complication of many types of advanced cancer, including breast cancer. Bone metastasis may cause severe pain, fractures, and hypercalcemia, rendering clinical management challenging and substantially reducing the quality of life and overall survival (OS) time of breast cancer patients. Studies have revealed that bone metastasis is related to interactions between tumor cells and the bone microenvironment, and involves complex molecular biological mechanisms, including colonization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 220 publications
0
14
0
Order By: Relevance
“…Approximately 70% of advanced breast cancer patients develop bone metastasis with the spine being the most common site 20,21 and recent studies indicate that breast cancer has a metastatic tropism to the spinal vertebral body 22 . To determine whether our findings could translate to a human breast cancer patient, single-cell RNA-sequencing of clinical specimens obtained from a radiologically normal and tumor-containing vertebral body ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 70% of advanced breast cancer patients develop bone metastasis with the spine being the most common site 20,21 and recent studies indicate that breast cancer has a metastatic tropism to the spinal vertebral body 22 . To determine whether our findings could translate to a human breast cancer patient, single-cell RNA-sequencing of clinical specimens obtained from a radiologically normal and tumor-containing vertebral body ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A 12-year cohort study in South Korea showed that the cumulative incidence of SRE in breast cancer patients was 47% [70]. Bone pain is the most common SRE, occurring in 80% of patients with bone metastases [65,71]. Hypercalcemia is the most lethal SRE and is associated with poor prognosis; it occurs in 10%-30% of patients with osteolytic lesions [72].…”
Section: Clinical Characteristics Of Breast Cancer Bone Metastasismentioning
confidence: 99%
“…There is an unambiguous negative correlation between bone metastasis and survival [ 6 ]; necessitating efficient methods to detect bone metastasis in a timely manner. Advancements in molecular imaging approaches has improved accuracy of diagnosis, staging and therapy response [ [7] , [8] , [9] ]. Clinical imaging of bone, including the bone marrow utilizes a spectrum of imaging modalities such as: X-ray based radiological planar and tomographic (computed tomography (CT)) imaging, high-spatial resolution magnetic resonance imaging (MRI), and nuclear imaging (single-photon emission computed tomography (SPECT) and positron emission tomography (PET)).…”
Section: Introductionmentioning
confidence: 99%